2001
DOI: 10.3133/ds63
|View full text |Cite
|
Sign up to set email alerts
|

The Putumayo-Oriente-Maranon Province of Colombia, Ecuador, and Peru; Mesozoic-Cenozoic and Paleozoic petroleum systems

Abstract: generation over the western third of the province, and pos sibly for gas generation in an area close to the western boundary of the Oriente and Maranon Basins. If these source rocks are thermally mature for gas generation, then some potential exists for gas reserves within low-permeability sandstone facies from nearshore marine and shoreface sandstones of the Cretaceous Napo, Chonta, and Agua Caliente Formations of the hypothetical Basin-Center Gas assessment unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…Niche conservatism also explains many aspects of ecological community assembly [28]. 2) The geologic events that resulted in the formation of natural tar seeps occurred during the late Miocene and early Pliocene and thus surface contamination with hydrocarbons has been a feature of western Amazonian forests for a long time [29]. In other words, the selective pressure favouring resistant genotypes have potentially been present for millions of years.…”
Section: Methodsmentioning
confidence: 99%
“…Niche conservatism also explains many aspects of ecological community assembly [28]. 2) The geologic events that resulted in the formation of natural tar seeps occurred during the late Miocene and early Pliocene and thus surface contamination with hydrocarbons has been a feature of western Amazonian forests for a long time [29]. In other words, the selective pressure favouring resistant genotypes have potentially been present for millions of years.…”
Section: Methodsmentioning
confidence: 99%
“…A regionally pervasive Miocene/Pliocene shortening, known as Quechua III (Higley 2000;Mathalone and Montoya 1995;Sébrier and Soler 1991) or as eu-Andean phase (Van der Hammen 1958), has been well documented by thrusting and compressional folding over most of the sub-Andean region in Peru, Ecuador and Colombia (Mathalone and Montoya 1995). This episode has been widely recognized as the main Andean orogenic uplift causing the present-day relief and related to the westward drift of South America and the progressive decrease in the age of crust entering the trench along the mountain belt (Pindell and Tabbutt 1995).…”
Section: Geologic Development Of the Basinmentioning
confidence: 99%
“…This basin is one of the most important oil regions in Colombia, where large hydrocarbon accumulations (i.e. Orito Field) have been discovered since the early 1940s (Higley 2000). Some wells revealed that mafic sills and dykes truncate the sedimentary succession.…”
Section: Introductionmentioning
confidence: 99%
“…The Oriente Basin of eastern Ecuador is part of the Upper Amazon River and is contiguous with the Putumayo basin of Colombia and the Marañon basin of Peru 4,5,6 . Mesozoic and Cenozoic sediments are preserved in Palo Azul field ( Figure 2).…”
Section: Geological Settingmentioning
confidence: 99%